Developing P-Stereogenic, Planar Chiral P-Alkene Ligands: Monodentate, Bidentate, and Double Agostic Coordination Modes on Ru(II) - Herrera, Alberto Cesar; Grasruck, Alexander; Heinemann, Frank Wilhelm; Scheurer, Andreas; Chelouan, Ahmed; Frierss, Sibylle; Seidel, Falk; Dorta, Romano (Organometallics, 2017)
10-Phenyl-5H-dibenz[b,f]azepine (5) is synthesized by Suzuki cross coupling of the protected bromo alkene 4 with PhB(OH)(2). 5 reacts with PCl3 to afford the dichlorophosphanyl-azepine 6 in >90% yield. Alkylation of 6 with 1 equiv of t-BuMgBr leads, after recrystallization in Et2O, to the diastereomerically enriched (dr > 98:2) chloride rac-7, which the crystal structure reveals to be the (pS,R-P)/(pR,S-P) pair. The fact that rac-7 crystallizes in the Sohncke space group P2(1)2(1)2(1) opens up the possibility of a mechanical separation of the enantiomers. Methylation of rac-7 is perfectly stereoselective with inversion of configuration at the P atom to yield the new ligand rac-8 as the (R,R)/(S,S) pair. The corresponding BH3-protected diastereomer rac-9 (i.e., the (R,S)/(S,R) pair), is isolated after flash column chromatography in 73% yield. Compounds 59 are accessible in multigram quantities. X-ray crystal structures of Ru(II) complexes demonstrate the ambidentate nature of ligand rac-8: Complex 10 is exclusively P-coordinated, while in complex 11 two ligands bind Ru through their P donors and stabilize the 14-electron metal center with a double agostic interaction. In complex 12, the ligand coordinates in a kappa P,eta(2)-alkene bidentate fashion.